Integrasi Pendidikan Karakter melalui Pembudayaan Sekolah di SD Muhammadiyah Wirobrajan 3 Yogyakarta - Asniyah Nailasariy (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
The objective of the article is to describe the implementation of character education through school culture, which was exemplified at SD Muhammadiyah Wirobrajan 3 Yogyakarta. The implementation of integrated character education in school culture is one of the alternatives to prevent deviant actions taken by the nation's children today. The method used in this research is descriptive analytic with a qualitative approach. The results showed that the character culture process could be integrated into various elements including; vision and mission of the school, professional leadership management, personnel commitment, utilizing teacher competence, cultivating positive attitudes, exemplary school members, adequate infrastructure, cultivating positive interactions, and building a comfortable atmosphere, and by maximizing school management patterns. Keywords: Integrative Character Education, School Culture